Capital, Technology, and Time. (30th April 2022) - Harris, Donald J
Abstract: This paper examines the substantive meaning and limitations of the concept of choice of technique, developed in the context of a test of logical consistency of the neoclassical parable concerning the relation between techniques of production and distribution of income in capitalist economies, and commonly used as a vehicle to support propositions about changes in technology. This concept is shown to rest on a foundation of logical time that is antithetical to a conception of historical time relevant to observed features of technological change. In this regard, it exposes a fundamental lacuna in the traditional neoclassical narrative and supporting theory related to the dual problems of agency and dynamics of the transition process involved in analysis of capital accumulation and technological change. There is room here for emerging alternative narratives to provide effective resolution of these problems.